Do Government Characteristics Affect E-Government Maturity? - Arief Rahman (Jurnal Reviu Akuntansi dan Keuangan, 2022)
The purpose of this research is to examine empirical evidence of the effect of human resource competence, information quality, government complexity, area, and size of government on the maturity of e-government of provincial government in Indonesia. The research applied purposive sampling method, and examined 21 provinces in Indonesia for the year of 2018-2020. This study uses secondary data from Central Bureau of Statistics, websites of provincial government, and data from Ministry of State Apparatus Empowerment and Reformation of Bureaucracy (KemenPAN RB). Since this research involved multiyear data, therefore data panel analysis using Common Effect Method was applied. The results show that human resource competence and government complexity significantly influence the maturity of e-government. However, information quality, width of area and size of government do not influence maturity of e-government. The results are important for the government in developing e-government systems. Implications of the research are further discussed in the paper.